Autoregulation in resistance training: a comparison of subjective versus objective methods - Shattock, K.; Tee, J. C. (The Journal of Strength and Conditioning Research, 2022)
Autoregulation (AR) is a resistance training periodization approach that adjusts training prescription in response to individual rates of athlete adaptation. AR training prescription can make use of either subjective (rating of perceived exertion [RPE]) or objective (barbell velocity) intensity descriptors. The aim of this research was to compare the efficacy of these 2 approaches in improving sport-specific physical performance measures. Using a randomized crossover design, 20 amateur rugby union players completed two 6-week blocks of training with training intensity prescribed using either objective velocity-based (VB) (measured using a wearable accelerometer device) or objective RPE-based intensity prescriptions. Training volume was matched for both groups while training intensity was equivalent but prescribed using either VB or RPE measures. Performance measurements were countermovement jump (CMJ), 1 repetition maximum back squat and bench press, and 10-, 20-, and 40-m sprint. Testing was conducted before and immediately after each training block. The likelihood that observed changes in performance measures were meaningful was assessed using magnitude-based decisions. Both training programs induced practically meaningful improvements in CMJ (VB most likely +8.2, ±1.1%; RPE likely +3.8, ±0.9%), back squat (VB most likely +7.5, ±1.5%; RPE possibly +3.5, ±1.8%), and bench press (VB most likely +7.7, ±2.1%; RPE possibly +3.8, ±0.9%). Changes in sprint test performance were very likely trivial for both programs. Objective AR programming resulted in larger improvements in CMJ (likely 4.2, ±1.2%), squat (likely 3.7, ±1.5%) performance, and bench press (possibly 3.7, ±1.5%) performance. Autoregulation periodization improved strength and CMJ, but not sprint performance. Autoregulation effects are augmented through the use of objective intensity prescription.